Fraudulent Financial Reporting: An Examination of Financial Stability, Financial Targets, and External Pressure - Abbas, Muhammad; Ilyas, Muhammad Khaidir (Amsir Management Journal, 2025)
This study addresses fraudulent financial reporting as a critical issue that threatens the integrity of financial information and undermines stakeholder trust in publicly listed companies. The objective of this research is to analyze the influence of financial stability, financial targets, and external pressure on the likelihood of fraudulent financial reporting in companies listed on the Indonesia Stock Exchange (IDX). This study employs a qualitative approach using inductive thematic analysis of non-numerical data, including corporate financial reports, academic literature, and relevant documents as primary data sources. The analysis is grounded in the theoretical frameworks of the fraud triangle, fraud pentagon, and fraud hexagon to identify and interpret the underlying drivers of financial statement fraud. The findings indicate that financial instability creates internal pressure on management to present financial conditions more favorably than their actual state. Additionally, unrealistic financial targets exacerbate the tendency toward manipulation. External pressures from investors, market expectations, and regulatory demands further intensify managerial motivation to manipulate financial data in order to maintain corporate reputation. Importantly, these three variables do not operate independently; rather, they interact and reinforce one another in creating an environment conducive to fraudulent behavior. This study highlights the importance of strengthening good corporate governance, implementing effective internal control systems, and fostering an ethical organizational culture as comprehensive mechanisms to prevent fraudulent financial reporting.